Correction of specimen strain measurement in Kolsky tension bar experiments on work-hardening materials. (October 2019) - Song, Bo; Sanborn, Brett; Susan, Donald; Johnson, Kyle; Dabling, Jeffrey; Carroll, Jay; Brink, Adam; Grutzik, Scott; Kustas, Andrew
Highlights: Dynamic tensile specimen strain measurements in a Kolsky tension bar test. Specimen strain correction method for linear work-hardening materials. Application of the new specimen strain correction method to Kolsky tension bar tests of Fe-49Co-2V alloy, 4140 steel, and 304L-VAR stainless steel. Abstract: Cylindrical dog-bone (or dumbbell) shaped samples have become a common design for dynamic tensile tests of ductile materials with a Kolsky tension bar. When a direct measurement of displacement between the bar ends is used to calculate the specimen strain, the actual strain in the specimen gage section is overestimated due to strain in the specimen shoulder and needs to be corrected. The currently available correction method works well for elastic-perfectly plastic materials but may not be applicable to materials that exhibit significant work-hardening behavior. In this study, we developed a new specimen strain correction method for materials possessing an elastic-plastic with linear work-hardening stress–strain response. A Kolsky tension bar test of a Fe-49Co-2V alloy (known by trade names Hiperco and Permendur) was used to demonstrate the new specimen strain correction method. This new correction method was also used to correct specimen strains in Kolsky tension bar experiments on two other materials: 4140 alloy, and 304L-VAR stainless steel, which had different work-hardening behavior.